Human Resource Management Strategy in Improving Organizational Performance - Triolita, Nina; Munawaroh, Enok; Nurhasanah, Nurhasanah; Al-Amin, Al-Amin (JAKI : Jurnal Akuntansi, 2025)
Human Resource Management (HRM) Strategy plays a crucial role in enhancing organizational performance by aligning human capital with strategic goals. This paper explores the significance of HRM strategies in fostering a high-performance work culture, focusing on how these strategies contribute to productivity, employee satisfaction, and overall organizational success. By analyzing various HRM practices, such as recruitment, training and development, performance appraisal, and employee engagement, the study underscores the importance of strategic alignment between HR policies and organizational objectives. The research adopts a qualitative approach, utilizing case studies and interviews with HR professionals from various organizations to gather insights on the implementation of HRM strategies. The findings reveal that the integration of HRM strategy with organizational goals ensures that the workforce is motivated, skilled, and well-equipped to meet the challenges in a dynamic business environment. Moreover, the paper examines how effective HRM strategies lead to improved employee retention, increased job satisfaction, and a reduction in turnover rates, which directly influences the overall performance of an organization. In conclusion, adopting a well-crafted HRM strategy is pivotal for organizations aiming to achieve sustainable growth and maintain a competitive edge in the market. The research emphasizes that HRM is not merely an administrative function but a strategic partner in organizational success